1995
DOI: 10.1111/j.1346-8138.1995.tb03889.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Comparative Study of the Antitumor Effects of Human Interferon‐α, β and γ on the Growth and Invasive Potential of Human Melanoma Cells

Abstract: We have studied the effects of interferon (IFN)-alpha, beta, and gamma in vitro on the growth and invasive potential of human melanoma SK-MEL-118 cells. The antiproliferative effects of IFNs were assessed by a quantitative regrowth assay in which cells were treated with IFNs at concentrations of 10(2), 10(3) or 10(4) IU/ml for 3 days (until day 4) and then further incubated without IFNs for 7 days (until day 11). The growth inhibitory effect of each IFN on melanoma cells was dose- and time-dependent. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…It seems to be an essential mediator not only for the host defense in the innate immune responses against microbial infections but also for a host defense system against oncogenesis (28). Few studies showed that IFN-h has greater antitumor effects than IFN-a via the activation of apoptosis (17)(18)(19)(20)(21). Therefore, IFN-h represents a promising drug in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems to be an essential mediator not only for the host defense in the innate immune responses against microbial infections but also for a host defense system against oncogenesis (28). Few studies showed that IFN-h has greater antitumor effects than IFN-a via the activation of apoptosis (17)(18)(19)(20)(21). Therefore, IFN-h represents a promising drug in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For all these reasons, novel treatment strategies seem mandatory. Few authors reported that IFN-h has greater antitumor effects than IFN-a on melanoma, squamous carcinoma, glioma, breast, and hepatocellular cancer (17)(18)(19)(20)(21). On these bases, IFN-h seems to be of potential interest in the treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus on hIFN-␤ because of its reported stronger antiproliferative activity against other tumor types. [11][12][13][14] The use of our immunodeficient model offers an opportunity to selectively assess the antiproliferative effects of hIFN-␤ in the absence of its immunomodulatory 15 and direct antiangiogenic properties, 16 because hIFN-␤ does not cross-react with its cognate murine receptor. 17 In our initial experiments, recombinant hIFN-␤ was administered either subcutaneously (2000 IU per mouse thrice weekly) or intravenously (60 000 IU per mouse daily) into cohorts of ␤2m null NOD/SCID mice a week after intravenous injection with HL-60 cells with an additional untreated cohort (n ϭ 10) serving as controls.…”
Section: Effects Of Ifn-␣ and ␤ On Aml Cell Lines In Vitro And In Vivomentioning
confidence: 99%
“…Notwithstanding IFN-␤ half-life (1 h) is shorter than that of IFN-␣ (4 -7 h), several studies showed that IFN-␤ has more potent antitumor effects than IFN-␣, via the activation of apoptosis (6,8,12,16,27,(31)(32)(33). In addition, new strategies could improve in future the pharmacokinetic and pharmacodynamic profile of IFN-␤, like the pegylated formulation (21).…”
Section: Discussionmentioning
confidence: 99%